Evaluation of cocoon silk as an annular closure material in a rodent disk model: Minimal behavioral burden despite pronounced inflammatory reaction - Friederike Weidemann; Sarah Strauß; Frederik Schlottmann; Mykola Fedchenko; Janin Reifenrath; Dorothea Daentzer (PLoS ONE, 2025)
Background Disk herniation is a common disease in the population. In case of relevant neurologic deficits and/or pain syndrome a surgical approach is necessary. Therefore, an incision has to be made in the outer ring of the disk to remove all parts of the prolapse. To date, a reliable closure device is missing and a recurrent herniation after a pain free interval is a postoperative problem well-known among spine surgeons. Methods The current study works on proof of concept and is the first of its kind that discusses cocoon silk as a possible closure material in intervertebral disk defects in a rat model. In addition, the burden of each animal due to the surgical procedure has been evaluated by Von Frey-filament testing and stress evaluation. Results The rats represented no or only minor stress response. In the filament testing the animals showed low-grade reactions in general as well. In the examination, inflammatory tissue response was detected directly to the silk, predominantly associated with macrophages. In some areas, cell death was visible. Conclusion The stress and pain impact on subjects after silk implantation as an annular closure device in a disk model in rat tails is negligible. The inflammatory reactions might be associated with remaining particles of the spider eggs, not the silk itself. Further investigations would be necessary to overcome this problem. Trial registration: All animal experimental protocols were approved by the Lower Saxony State Office for Consumer Protection and Food Safety (LAVES; Approval No 33.8-42502-04-21/3771)